2009
DOI: 10.1007/s10865-009-9232-5
|View full text |Cite
|
Sign up to set email alerts
|

Taking into account the observers’ uncertainty: a graduated approach to the credibility of the patient’s pain evaluation

Abstract: 1 AcknowledgementsAuthors wish to thank John Burns and three unknown referees for their pertinent comments and suggestions. We are also grateful to Marco Marelli for his suggestions on the analyses of the properties of the graduated approach used in Experiment 2. 1 AbstractThis article presents two experiments aiming to investigate the adoption of a graduated measure to describe credibility attribution by observers who evaluate patients' pain accounts. A total of 160 medical students were required to express a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this regard, there remains a lack of empirical research on the cognitive underpinnings of pain miscalibration. 11e13, 49 The present study is an attempt to unveil a cognitive process that might intervene in pain assessment. We focused on the use of a readily accessible heuristic, namely anchoring and adjustment, whereby people rely excessively on an initial impression and interpret subsequent incoming evidence with reference to that impression.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, there remains a lack of empirical research on the cognitive underpinnings of pain miscalibration. 11e13, 49 The present study is an attempt to unveil a cognitive process that might intervene in pain assessment. We focused on the use of a readily accessible heuristic, namely anchoring and adjustment, whereby people rely excessively on an initial impression and interpret subsequent incoming evidence with reference to that impression.…”
Section: Discussionmentioning
confidence: 99%
“…54 Uncertainty in accepting or acting on individual self-reports is particularly increased in the presence of high pain scores and ambiguous behavioral or physical signs or symptoms. 52,54 These findings are not surprising, given that a large part of general interpersonal communication is nonverbal.…”
Section: Nurse Scrutiny: a Critical Undertow In Pediatric Acute Pain Management Decisionsmentioning
confidence: 92%
“…51 This finding is similar to a study of medical students who believed the patient's pain report to be credible in only 45% of cases. 52 In another survey, 55% of pediatric nurses reported that at least 20% of children likely overreport their pain. 53 Potential reasons for discordant judgments include incongruent presentation, provider uncertainty, and provider bias.…”
Section: Nurse Scrutiny: a Critical Undertow In Pediatric Acute Pain Management Decisionsmentioning
confidence: 99%
“…Additionally, research has demonstrated that women are less likely to get appropriate referrals when presenting with chronic pain of an unknown etiology (Stalnacke et al, 2015). Furthermore, female pain intensity is less likely to be believed, even when presenting with similar physical signs as males (Rusconi et al, 2010).…”
mentioning
confidence: 99%